Change Financing Mechanisms of Health Institutions under the Branch Reform - Чала, Н. Д. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
This article considers the impact of expected changes in the macro and microenvironment on the mechanisms of financing the health care. Most of attention is focused on the challenges hospitals face after getting autonomy in particular noted that the bill does not sufficiently clearly define mechanisms of bankruptcy of medical institutions.